Identifikasi Regulasi Peningkatan Investasi dan Perluasan Lapangan Kerja di Kabupaten Malang: - Kusmayadi, Rudy Catur Rohman (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
This research identifies and seeks answers to problems regarding investment regulation and job creation from the perspective of Islamic Sharia, regulations governing regional security and order from all activities that cause social and political disturbances, regulations as Government Intention that represent support for investment opportunities and expansion employment opportunities in Malang Regency to help and facilitate the expansion of employment opportunities